Is It Useful and Necessary to Add a T2 Paravertebral Block to the Regional Anesthesia During Proximal Humeral Fracture Surgery in Elderly Patients? A Prospective and Randomized Controlled Trial - Wang, Xiaofeng; Zhang, Hui; Chen, Yongzhu; Zhang, Qingfu; Xie, Zhenwei; Liao, Junling; Jiang, Wei; Zhang, Junfeng (Frontiers in Surgery, 2022)
Objective: This study was designed to investigate whether it is useful and necessary to add a T2 level thoracic paravertebral block (TPVB) on the basis of brachial-cervical plexus block to avoid incomplete anesthesia in the elderly patients undergoing deltopectoral approach proximal humeral fracture (PHF) surgery. Materials and Methods: Eighty patients scheduled for PHF surgery were randomized to receive either IC block (combined interscalene brachial plexus with superficial cervical plexus block) or ICTP block (T2 TPVB supplemented with IC block). The primary outcome was the success rate of regional anesthesia. The patient who experienced incomplete block was administered with intravenous remifentanil for rescue, or conversion to general anesthesia (GA) if remifentanil was still ineffective. Secondary outcomes included requirements of rescue anesthesia, sensory block of surgical region, incidence of adverse reactions, and block procedure related complications. Results: The success rate of regional anesthesia in ICTP group was higher compared with IC group (77.5 vs 52.5%, p=0.019). Intravenous remifentanil was required in 32.5% of patients in IC group and 17.5% in ICTP group, respectively. Conversion to GA was performed in 15% of patients in IC group and 5% in ICTP group. Sensory block at the medial proximal upper arm was achieved in 85% of patients in ICTP group, whereas 10% in IC group (p<0.001). There was no difference between the groups with respect to incidence of intraoperative adverse reactions. No block related complications occurred in either group. Conclusions: Adding a T2 TPVB is helpful to decrease, but not absolutely avoid the occurrence of incomplete regional anesthesia during PHF surgery in the elderly patients. However, considering the potential risks, it is not an ideal option while minor dose of remifentanil can provide a satisfactory rescue effect.